The relation between sexual self-concepts and attachment styles in married women: A cross-sectional study - Maryam Mohammadi Nik; Maryam Modarres; Tayebeh Ziaei (Tehran University of Medical Sciences, 2018)
Background &Aim: Sexual self-concept is providing recognition of sexual aspects of each person, which is derived from previous experiences, points out the recent experience and guides the sexual behaviors. The aim of the present study was to evaluate the relation between sexual self-concept and attachment styles in married women who referred to the health centers of Tehran in 2014. Methods & Materials: This descriptive analytical cross-sectional study was conducted on 365 women of reproductive age (15 to 44 years old) who referred to the health centers affiliated with Tehran University of Medical Sciences. Data gathering tools were demographic characteristics questionnaire, the standard questionnaire for sexual self-concept and the standard questionnaire for attachment. Data were analyzed by SPSS version 16 using descriptive statistics and Pearson correlation coefficient with a significant level of α = 0.05. Results: Results showed a direct correlation between negative sexual self-concept and anxious attachment (p < 0.0001) and avoidant attachment (p < 0.0001) and a reverse correlation between negative sexual self-concept and secure attachment (p < 0.0001). In contrary, positive sexual self-concept had a reverse correlation with anxious attachment (p = 0.006) and avoidant attachment (p = 0.114) and a direct correlation with secure attachment (p = 0.006). Conclusions: Considering the direct correlation between positive sexual self-concept and secure attachment and also between negative sexual self-concept and non-secure attachment (anxious and avoidant), it is predicted that by appropriate planning for secure attachment, health sexual behaviors could be reached.